Flexural behaviour of corrugated panels of self-reinforced polypropylene hybridised with carbon fibre: An experimental and modelling study. (15th November 2018) - Mesquita, Francisco; van Gysel, Anke; Selezneva, Marina; Swolfs, Yentl; Lomov, Stepan V.; Gorbatikh, Larissa
Abstract: The present work investigates the influence of the laminate layup on the flexural properties and failure mechanisms of corrugated panels made of self-reinforced polypropylene (SRPP) hybridised with carbon fibre. The influence of the layup on the stiffness and strength of the corrugated hybrid composite panels was much less important than the carbon fibre content. The experimental program was complemented by finite element analysis. The model revealed the importance of SRPP's non-linear behaviour and difference in tensile and compressive behaviour in controlling the flexural properties of corrugated panels. The compressive behaviour of SRPP was characterised to provide reliable input data for the model.